2011
DOI: 10.1007/s10904-011-9592-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Thermally Stable and Biologically Active Metal-Based Schiff Base Polymer

Abstract: Schiff base was prepared via condensation of ethanedihydrazide with 2-hydroxy benzaldehyde and further this monomeric Schiff base polymerize with formaldehyde and barbituric acid and form polymeric Schiff base (PLSB) ligand. The ligand and its polymer metal complexes were characterized by using elemental analysis, IR, UV-VIS, 1 HNMR, magnetic susceptibility and thermogravimetric studies. On basis of elemental analysis and spectral studies, six coordinated geometry was assigned for Mn(II), Co(II) and Ni(II) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Main-chain polymeric Schiff bases were prepared through a condensation reaction. 92 Then, the target metal-containing polymer can be prepared in quantitative yields by interacting with an equimolar amount of transition metal salts (Mn(II), Co(II), Ni(II), Cu(II) and Zn(II)). Compared with the polymeric Schiff bases, Parveen et al found that all of these metalcontaining polymeric compounds showed enhanced antibacterial activity against E. coli, B. subtilis, S. aureus, P. aeruginosa and S. typhi, and antifungal activity against T. longifusus, C. albicans, M. canis, F. solani and C. glaberata.…”
Section: Antimicrobial and Antiviral Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Main-chain polymeric Schiff bases were prepared through a condensation reaction. 92 Then, the target metal-containing polymer can be prepared in quantitative yields by interacting with an equimolar amount of transition metal salts (Mn(II), Co(II), Ni(II), Cu(II) and Zn(II)). Compared with the polymeric Schiff bases, Parveen et al found that all of these metalcontaining polymeric compounds showed enhanced antibacterial activity against E. coli, B. subtilis, S. aureus, P. aeruginosa and S. typhi, and antifungal activity against T. longifusus, C. albicans, M. canis, F. solani and C. glaberata.…”
Section: Antimicrobial and Antiviral Agentsmentioning
confidence: 99%
“…They attributed the enhanced activity to the coordination interaction with metal ions. 92,93 Germanium and its derivatives have been utilized for dietary supplements, immunity enhancement and antimicrobial materials. [94][95][96] Based on their unique properties, germaniumcontaining polymers were also investigated.…”
Section: Antimicrobial and Antiviral Agentsmentioning
confidence: 99%
“…They are synthesized by polycondensation reaction between diamine and dialdehyde or diketone [10]. They are an important category of compounds and useful complexing ligands for a number of transition metal ions and indicate paramagnetism, semiconducting and resistance to high energy [11,12]. They are used to prepare composite materials having high resistance at high temperatures, thermostabilized, photoresistors, flame resistance materials, and components of electrochemical cells.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 They are an important class of compounds and find their application in different fields. They are useful complexing ligands for a number of transition metal ions 8,9 and indicate paramagnetism, semiconducting and resistance to high energy. [10][11][12][13] They are used to prepare composite materials having high resistance at high temperatures, thermostablizers, photoresistors, flame resistance materials, and components of electrochemical cells.…”
Section: Introductionmentioning
confidence: 99%